Situation Method In Learning Arabic In The Era Of Industrial Revolution 4.0 - Ahyani, Hisam (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2021)
This research is motivated by several problems in the teaching and learning process without where a teacher or lecturer uses the method, it will not progress and develop and will have difficulty achieving a goal expected from the teaching and learning process. Departing from this problem, the author wishes to describe the learning methods in Arabic courses and analyze these learning methods, of course, the learning method used is a method that is very relevant and up to date and suitable in this 4.0 Industrial Revolution Era. The Arabic language course can be said to have quite complicated characteristics, so in this learning it needs a lot of memorization that allows students to master the Arabic language material. However, it should be noted that in the teaching and learning process there should be no emphasis because this will make the student's psyche weak. For this reason, the authors consider the Situation Method as the answer. This method is applied to make it easier for students to learn Arabic in general.Keywords: Situation Method, Learning Approach, Arabic